IMPLEMENTASI SISTEM MANAJEMEN MUTU DALAM BIDANG KURIKULUM - Yayu Marita (Manajer Pendididikan, 2020)
This paper described the implementation of Management Quality System ISO 9001: 2008 in the curriculum at Special Education of Bengkulu City. This study used descriptive qualitative method. The subject of this study is headmaster, vice principal curriculum, and teachers. The data collection do the interview, observation, and documentation study. The result of this study indicate the implementation of Quality Management System ISO 9001: 2008 in curriculum part has not been implemented in based on prosedur given by Management Quality System ISO 9001: 2008.